Prevalence and risk factors of gastroesophageal reflux disease among adults attending primary healthcare in Bahrain - Dhuha F. Alqassab; Maryam J. Hasan; Ayman M. AlSaadoon; Aysha J. AlMuqahwi; Farah A. AlAwadhi; Samya A. Bahram; Adel S. Alsayyad (Journal of Family Medicine and Primary Care)
Background: Gastroesophageal reflux disease (GERD) is one of the most diagnosed digestive disorders, with much-conducted research assessing its prevalence and risk factors associated with it worldwide. However, there are no published previous studies to determine such disease and its burden in Bahrain. Hence, this study aims to estimate the prevalence and evaluate the risk factors associated with GERD among adults attending primary care in Bahrain. Material and Methodology: A total of 385 adults aged 18 years and above participated in this descriptive cross-sectional study in the period from 1st to 27th of April 2023. The sample was collected randomly through an interview-based validated questionnaire from 10 health centers selected randomly. The questionnaire consisted of three sections: Demographic characteristics, risk factors that are associated with GERD and (GERD-Q) questionnaire with a scoring rate for the diagnosis of GERD, in which a score of 8 or more gives us the diagnosis of GERD. Results: A response rate of 93.6% was accomplished. Most of the participants were female (53.2%), Bahraini (88.6%), university-educated (50.9%) and married (71.2%). The mean age of the participants was 41.5 (SD = ±14.4 years). The prevalence of GERD was 41.5% which was statistically significant associated with family history of GERD, history of hypertension, sleeping within less than 1 hour after dinner, bariatric surgery and use of NSAIDs or Aspirin regularly (P < 0.05). Conclusions: The prevalence of GERD was 41.5%, which is higher than in the Middle East, East Asia and Western countries. Many modifiable risk factors where associate with it which deserves the conduction of national prevention programs and educational campaigns to prevent this disease and its complications. Further studies are needed to assess other risk factors and the effect of GERD on the overall health status and quality of life.